2018
DOI: 10.1002/app.47269
|View full text |Cite
|
Sign up to set email alerts
|

Big effects of small nanoparticles on hydrophobically modified polyacrylamide in an aqueous solution

Abstract: In this study, we investigated the self‐assembly properties of small‐sized (3–5 nm) oppositely charged SiO2 nanoparticles (NPs) and hydrophobically modified polyacrylamide (hm‐PAM) in aqueous solutions by rheological and structural analysis. The results show that the addition of small NPs to the hm‐PAM solution remarkably enhanced its viscosity and viscoelasticity, and the viscosity remained high at elevated temperatures. Specifically, the low shear rate viscosity of the NP–hm‐PAM solutions increased by up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…They also found that the CAC of XG-C16 was 1600 ppm, and starting at this concentration, there was a significant increase in the viscosity of the solution, indicating the association of the hydrophobic groups of the modified polymer. Peng et al (2019) studied the effect of adding silica nanoparticles in hydrophobically modified polyacrylamide with N, N-dimethyl octadecyl ammonium groups (NP-HMAP) and found that the presence of silica improved the viscosity and viscoelasticity of the polymeric solution at high temperatures. Thus, the addition of nanofillers was cited as a way to further improve the properties of hydrophobically modified polymers.…”
Section: Hydrophobically Modified Associative Polymers (Hmaps)mentioning
confidence: 99%
“…They also found that the CAC of XG-C16 was 1600 ppm, and starting at this concentration, there was a significant increase in the viscosity of the solution, indicating the association of the hydrophobic groups of the modified polymer. Peng et al (2019) studied the effect of adding silica nanoparticles in hydrophobically modified polyacrylamide with N, N-dimethyl octadecyl ammonium groups (NP-HMAP) and found that the presence of silica improved the viscosity and viscoelasticity of the polymeric solution at high temperatures. Thus, the addition of nanofillers was cited as a way to further improve the properties of hydrophobically modified polymers.…”
Section: Hydrophobically Modified Associative Polymers (Hmaps)mentioning
confidence: 99%
“…Moreover, it has a high surface area which is beneficial in providing a more stable structure through increasing the tie points between the polymer entanglement . Nanosilica increases the long-term stability of the modified hydrophobic PAM to more than 18 months . Increasing the temperature enhances the adsorption of PAM on the silica surface .…”
Section: Introductionmentioning
confidence: 99%
“…14 Nanosilica increases the long-term stability of the modified hydrophobic PAM to more than 18 months. 15 Increasing the temperature enhances the adsorption of PAM on the silica surface. 16 Nonfunctionalized silica contains a silanol group, and other types of materials such as sodium silicate have been used as reinforcement agents.…”
Section: Introductionmentioning
confidence: 99%